1993
DOI: 10.1128/jb.175.3.630-635.1993
|View full text |Cite
|
Sign up to set email alerts
|

The product of the hypB gene, which is required for nickel incorporation into hydrogenases, is a novel guanine nucleotide-binding protein

Abstract: The products of the hyp operon genes are essential for the formation of catalytically active hydrogenases in Escherichia coli. At least one of these auxiliary proteins, HYPB, appears to be involved in nickel liganding to the hydrogenase apoprotein, since mutations in hypB can be phenotypically suppressed by high nickel concentrations in the medium (R. Waugh and D. H. Boxer, Biochimie 68:157-166, 1986). To approach the identification of the specific function of HYPB, we overexpressed the hypB gene and purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
169
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 22 publications
10
169
0
Order By: Relevance
“…It is still unknown in which oT der these processes take place and whether further reactions a e required. It has been shown that nickel insertion into the p:ecursors is a prerequisite for the large subunit C-terminal p~ ocessing of the hydrogenase of A. vinelandii [23], HYD1 [24] a~Ld HYD3 of E. coli [25]. In this communication, we show tlat the intracellular availability of nickel is essential for I-i YD2 translocation to the periplasmic side of the membrane.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is still unknown in which oT der these processes take place and whether further reactions a e required. It has been shown that nickel insertion into the p:ecursors is a prerequisite for the large subunit C-terminal p~ ocessing of the hydrogenase of A. vinelandii [23], HYD1 [24] a~Ld HYD3 of E. coli [25]. In this communication, we show tlat the intracellular availability of nickel is essential for I-i YD2 translocation to the periplasmic side of the membrane.…”
Section: Discussionmentioning
confidence: 62%
“…The gene p~ oducts of the hyp operon are required for the maturation of c~ talytically active hydrogenases [18]. Among them, the HypB protein exhibiting a low intrinsic GTPase activity is directly ii volved in nickel insertion into the precursor of the large st bunit of HYD3 and its processing [25,26]. Proteins homolc~gous to HypB are also found in Rhodobacter capsulatus, 1,4tizobium leguminosarum, A. vinelandii and Alcaligenes eutropros (for a review, see [27]).…”
Section: Discussionmentioning
confidence: 99%
“…This protein is required for the formation of active hydrogenases but does not regulate the expression of the structural genes (Tibelius et al, 1993); rather it is thought to be part of a system involved in the incorporation of nickel into the hydrogenase, a prerequisite for processing to produce active enzyme (Rossman et al, 1994). This conclusion is based in part on the observations that a hypB mutant of E. coli could be complemented by high concentrations of nickel ion in the medium (Lutz et al, 1991) and also that such a mutant accumulated inactive precursor hydrogenase 3 large subunit which was devoid of nickel (Maier et al, 1993). The M. smegmatis orf1 product includes a histidine-rich region with potential nickel binding capacity in common with several other related proteins involved in processing nickel-containing enzymes; HypB of E. coli does not contain such a region, however.…”
Section: Discussionmentioning
confidence: 99%
“…The core machinery, as demonstrated for the synthesis of the intracellularly located hydrogenase 3 from E. coli, consists of the products of the six hyp genes plus an endopeptidase ( [1][2][3][4] and for review see [5,6]). The two hyp gene products HypA and HypB together with the auxiliary protein SlyD [7][8][9] are required for nickel sequestration and incorporation, whereas the four other Hyp proteins (HypC to HypF) are involved in synthesis of the CN ligand and the cyanation of the active site iron [10][11][12][13]. The source and biosynthesis of the CO ligand are still unknown [14].…”
Section: Introductionmentioning
confidence: 99%